Bayerisches Jahrbuch. Auskunfts- und Adressenwerk. (Bayerisches Jahrbuch, 2014)
Up-to-date information on some 7,000 institutions and approx. 12,000 persons in public life in Bavaria: authorities and departments of local, state and federal administration jurisdiction syndicates and other organizations from politics, business, academic life, the arts etc. notaries, church offices, universities, museums, libraries, banks mayors, District Administrators, chairpersons, managing directors and other executives.